Variation in the Mu-Opioid Receptor (OPRM1) and Offspring Sex Are Associated With Maternal Behavior in Rhesus Macaques (Macaca mulatta) - Wood, Elizabeth K.; Baron, Zachary; Schwandt, Melanie L.; Lindell, Stephen G.; Barr, Christina S.; Suomi, Stephen J.; Higley, J. Dee (Frontiers in Behavioral Neuroscience, 2022)
A m-opioid receptor (OPRM1) single-nucleotide-polymorphism, found in both humans and rhesus macaques mediates the mother-infant attachment bond. Because mothers treat their sons and daughters differently, it is somewhat surprising that the role of infant sex has not been assessed in the context of a maternal-OPRM1-genotype-by-infant-sex interaction. The present study investigates the effect of maternal-OPRM1-genotype and infant sex on mother-infant behaviors. Over the first six months of offspring life, mother-infant behavioral data assessing attachment quality was collected twice weekly from a large number of rhesus monkey mother-infant pairs (N=161 dyads; n=64 female infants, n=97 male infants). Mothers were genotyped for OPRM1 variation. Factor analysis of the observed behaviors showed two factors: Attachment (maternal-infant cradling, rejections, and infant approaches and leaves), and Maternal Restraints (mother restrains infant, preventing exploration). Further analyses showed a two-way, maternal-genotype-by-infant-sex interaction for both factors. For Attachment, mothers with the CC genotype cradled and restrained (Maternal Restraints) their female infants more and rejected them less, when compared to female infants of CG mothers. Perhaps as a consequence, female infants of CC genotype mothers approached and left their mothers less often, when compared to female infants of CG mothers, likely an indication that female infants from mothers with CG genotype play a greater role in maintaining the mother-infant bond than do female infants from CC genotype mothers. This finding may also indicate a more secure attachment in infants from CC genotype mothers. Unlike female infants, on average, the mother-infant relationship of dyads with a male infant was largely undifferentiated by maternal genotype. These findings suggest that, in contrast to female infants from CG mothers, CC mothers and their female infants appear to have a closer mother-infant relationship which may portend close life-long bonds, as mothers and female offspring remain together throughout life. Male offspring appear to have a more aloof mother-infant bond regardless of OPRM1-genotype. The results of this study indicate that maternal-OPRM1 variation mediates mother-infant attachment behaviors for female infants, and has less effect for male infants. This suggests that offspring sex should be included in studies investigating the effect of maternal-OPRM1 genotype on the mother-infant attachment relationship.